The Garden of Entangled Paths: Landscape Phenomena at the Albany Bulb Wasteland - Karl Kullmann (Landscape Review, 2017)
Over four decades, the Albany Bulb in the San Francisco Bay Area, California, United States of America metamorphosed from a dumpsite to a thicket harbouring a clandestine community. Since the forced decampment of this spontaneous society, the site has endured as a living ruin that continues to inspire the explorative impulses of visitors. While residual structures and decaying scrap-sculptures represent the tangible face of the site and its heterotopic past, more nuanced underlying landscape phenomena ground this cultural legacy. In exploring these phenomena, this paper offers a counterpoint to the tendency to engage with wastelands programmatically and pictorially while overlooking the influence of the corporeal landscape. The emergent nature of these phenomena suggests that the agency of design might circumvent typically fraught interactions with undesigned waste-scapes by assuming characteristics of the gardener.